(untitled) (American International Journal of Supply Chain Management, 2023)
In the contemporary workplace, where diversity in learning styles and preferences is paramount, understanding and enhancing the effectiveness of training programs has become critical for organizational success. This study investigates trainee reactions to employee training programs, emphasizing the dimensions of Perceived Training Efficiency (PTE), Perceived Trainer Performance (PTP), and Perceived Usefulness of Training (PUT). The research employs a quantitative approach, surveys 381 employees using stratified random sampling from eight private commercial banks in Bangladesh, and uses a structured questionnaire with a Likert scale. The study utilizes descriptive and inferential statistics. Findings reveal positive perceptions in terms of training efficiency and trainer performance. However, the perceived usefulness of training shows room for improvement. The statistical significance of the results confirms their applicability to a broader population. The study’s implications suggest a need for adaptive strategies in organizational training initiatives. Continuous feedback mechanisms are advocated to refine training programs in real time, emphasizing the personalized training approaches that align with diverse learning needs and career aspirations. This study acknowledges its limitations and calls for multiple evaluation methods and comparative analysis for the assessment of training programs JEL Classification Codes: I23, M12, M53.